2011
DOI: 10.1007/s00429-011-0336-7
|View full text |Cite
|
Sign up to set email alerts
|

Cellular markers of neuroinflammation and neurogenesis after ischemic brain injury in the long-term survival rat model

Abstract: MRI was employed to follow the neurodegenerative foci and the localization of inflammatory cells by magnetically labeled CD4+ or CD8+ lymphocytes in the ischemia/reperfusion long-lived rats (9 and 13 months after 10 min of cardiac arrest). MRI of ischemic rats showed: (1) blood-brain barrier (BBB) leakage in the area of the dorsal hippocampus and brainstem-hindbrain level in basal cerebellum, (2) unlike anti-CD8 magnetic antibodies anti-CD4 ultra small paramagnetic iron oxide particles (USPIO) antibodies revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
147
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 89 publications
(152 citation statements)
references
References 39 publications
5
147
0
Order By: Relevance
“…This change is based mostly on facts accumulated recently, indi-Ryszard Pluta, Anna Bogucka-Kocka, Marzena Ułamek-Kozioł, Wanda Furmaga-Jabłońska, Sławomir Januszewski, Judyta Brzozowska, Mirosław Jabłoński, Janusz Kocki cating that neural stem/progenitor cells occupy two main regions, the subventricular zone of the lateral ventricles and the subgranular zone of the dentate gyrus in the hippocampus, where they give rise to neurons after birth [30,38,54,58]. Neurogenesis has been found in these brain areas in all mammalian species, including humans [9,30,38,54,58], and may serve to replace brain cells damaged by insults. Two discrete brain regions presented contain progenitor cells that are capable of differentiating into neuronal or glial cells.…”
Section: The Importance Of Hippocampal Neurogenesis In Postischemic Bmentioning
confidence: 99%
See 4 more Smart Citations
“…This change is based mostly on facts accumulated recently, indi-Ryszard Pluta, Anna Bogucka-Kocka, Marzena Ułamek-Kozioł, Wanda Furmaga-Jabłońska, Sławomir Januszewski, Judyta Brzozowska, Mirosław Jabłoński, Janusz Kocki cating that neural stem/progenitor cells occupy two main regions, the subventricular zone of the lateral ventricles and the subgranular zone of the dentate gyrus in the hippocampus, where they give rise to neurons after birth [30,38,54,58]. Neurogenesis has been found in these brain areas in all mammalian species, including humans [9,30,38,54,58], and may serve to replace brain cells damaged by insults. Two discrete brain regions presented contain progenitor cells that are capable of differentiating into neuronal or glial cells.…”
Section: The Importance Of Hippocampal Neurogenesis In Postischemic Bmentioning
confidence: 99%
“…Since neurogenesis is required for memory and learning, and its activity has shown to be decreased after ischemia in humans and rodents [25,26], it has been suggested that impaired hippocampal neurogenesis might be an integral part of postischemic progression [58]. Particularly, a variety of key factors involved in brain ischemia, among them presenilin 1 and 2, amyloid precursor protein and its products β-amyloid peptides, play either a positive or a negative role in hippocampal neurogenesis [7,27].…”
Section: The Importance Of Hippocampal Neurogenesis In Postischemic Bmentioning
confidence: 99%
See 3 more Smart Citations